2004
DOI: 10.1016/j.jcrs.2003.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Phakic intraocular lenses to correct high myopia

Abstract: There was a higher incidence of anterior subcapsular cataract formation in the Adatomed group than in the Staar group. Delayed cataract development and the cataract type in patients with Artisan IOLs indicate that age and axial length may be prognostic factors. Factors such as IOL design, material, and placement probably affect cataract formation in eyes with posterior chamber IOLs for high myopia, particularly the Adatomed IOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
2
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(82 citation statements)
references
References 25 publications
1
75
2
4
Order By: Relevance
“…The Verisyse/Artisan anterior-chamber IOL has a low incidence (2%) of cataract progression in adults. 12,42,44 Pig-…”
Section: Volume 12 Number 3 / June 2008mentioning
confidence: 99%
“…The Verisyse/Artisan anterior-chamber IOL has a low incidence (2%) of cataract progression in adults. 12,42,44 Pig-…”
Section: Volume 12 Number 3 / June 2008mentioning
confidence: 99%
“…The two enclavation sites, located 180° apart, serve to support stable fixation of the lens while permitting relatively unrestricted movement of the pupil. A number of studies have been published in the literature demonstrating the safety and efficacy of the Artisan phakic IOL for the correction of myopia [5,6,7], hyperopia [10,11,12] and astigmatism [4,13]. It is estimated that over 100,000 Artisan phakic IOLs have been implanted worldwide to date.…”
Section: Discussionmentioning
confidence: 99%
“…Initially developed by Fechner and Worst in 1978, the iris claw lens was modified to a convex-concave configuration in 1991 [1,2]. A number of studies have shown these lenses to be safe and effective for refractive error correction [3,4,5,6,7,8]. We report a 5-year prospective study of patients who underwent Artisan (Ophtec BV, Groningen, The Netherlands) phakic IOL insertion for the correction of myopia, hyperopia and astigmatism at our unit.…”
Section: Introductionmentioning
confidence: 99%
“…4 Subsequently manufacturers have advised securing the dog leash with a secondary security collar. 5 Although this may appear to be an inconvenient second step, the benefits far outweigh the risk of permanent sight loss. It is also important to choose a type of leash that is adjusted to the size, weight, and force of the animal.…”
Section: Commentmentioning
confidence: 99%